How Well Do Occupational Therapy Competencies Support the Transition Into Health Service Management and Leadership? - Coles, Jennifer (Auckland University of Technology, 2024)
Purpose: While many health professionals are employed as health service managers in District Health Boards (DHBs), little is known about the competencies (skills, knowledge, and attitudes) occupational therapists carry forward from their professional education and the management competencies they are least prepared for when transitioning into these roles. The questions at the centre of this thesis are: “What do occupational therapists employed in health service management roles in the DHBs identify as the core management competencies they developed through their professional training and experience?” and “What were the competencies required in their management role that they perceived they were least prepared for?” The research objectives were to conduct an exploratory study to generate new knowledge that is useful to health professionals, their professional associations, the health services that employ them, registration bodies, and undergraduate and postgraduate educational providers by informing competency identification and development initiatives. Method: The research methodology, interpretive description, informed by the writing of Dewey (1859-1952) and Thorne (1951- ), was selected because of the emphasis on individual experiences and learning in the health workplace, and the inclusion of the researcher’s experiences and knowledge. Twelve participants with experience as occupational therapists and in health service management roles were interviewed. Data were collected through one interview with each participant and the collateral material they provided. Data analysis utilised inductive thematic and abductive methods. Findings: Four themes were developed from the data analysis: occupational therapy competencies employed, management competencies least prepared for, career journey, and ongoing competency development. Key findings are that occupational therapy competencies of perspective, approach, and attitude; clinical, technical, and operations skills; and culture and sector knowledge, are employed in health service management, but their professional education does not fully prepare occupational therapists for all competencies required for management. Core competency domains of leadership, business, and administration; managing within the healthcare environment; and building self-confidence and resilience were identified as least prepared for. The research revealed that line managers and mentors play a vital role in creating a supportive learning environment for aspiring and emerging managers, and the provision of challenging service opportunities is crucial to developing new skills, knowledge, and attitudes. The study also found that further competency development was primarily self-directed via informal workplace learning. Finally, the findings suggest that annual performance review and competency assurance processes are limited in their applicability and usefulness to health service managers’ ongoing competency development. Conclusions: There would be value in individual occupational therapists in managerial positions being able to identify and communicate the competencies they possess from their professional education and experience, and which they bring to health service management. The benefit of this knowledge is the confidence that they are not restricted to clinical practice and can show alignment between occupational therapy competencies and the requirements for effective health service management. There would also be value in targeted competency development informed by the areas of competence that occupational therapy managers identify they lack and where competency gaps may emerge. This knowledge will support the transition into management by targeting known competency gaps and minimising training in areas of existing competence. While the findings are specific to occupational therapy, they suggest that there would be value to individual managers, organisations, and the health sector as a whole from establishing competency development programmes, including programmes at university level, to support and prepare individuals for career opportunities and role responsibilities in the transition from clinician to manager. Such a programme can be informed by the knowledge of competencies developed from previous professional education and competency frameworks, and the competency gaps. Overall, health professionals have skills, knowledge, and attitudes developed from their professional education and sector experience that are applicable in health service management; however, further competency development is required. This knowledge supports the position that health professionals should consider health service management as a career option for which they are already partially prepared.